KONSEP TEOLOGI DIAKLETIS SHAYKH NAWAWI AL BANTANI: UPAYA PREVENTIF RADIKALISME ATAS EKSISTENSI KEMAJEMUKAN DI NUSANTARA - Ubaidillah Ubaidillah (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2017)
Radicalism threatens the stability of the sovereignty of Indonesian nation and state based on Pancasila and the 1945 Constitution. Pursuant to the spirit of puritanism wants to develop dar al-Islam and dar al-harb in Indonesia in the model of religious expression. Yet, along with the growth of radicalism, Indonesian Islam actually presents the ideal Islamic image as the Islamic concept of rahmatan lil 'Alamin, which sees cultural, religious, ethnic and racial diversity not as a threat but a harmony that gives a unique and unique cultural color. In the context of religion, it is necessary to re-read the framework of the concept of kalam Shaykh Muhammad Nawawi al-Bantani in tafsir al-Munir to answer the question of how the concept of kalam in interpreting diversity and how the significance of the concept provides justificationfor a diversity and how efforts can be done in keeping And care for the religion as the wealth of the archipelago. Keywords: Theological Concepts, Radicalism and Diversity, Nawawi al- Bantani